APPROACHES AND METHODS TO LANGUAGE TEACHING: A REVIEW - Ramanjaney Kumar Upadhyay (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Although what we say below applies to all languages, we are essentially dealing with the teaching of English as a second language is the focal point of the review paper. What we present below is a brief review of the major approaches and methods to (English) language teaching and how these have a role to play in the overall communicative abilities of learners. The approaches and methods stem out of the thinking dominant in a particular time period. Which is why, it is easy to see a direct correlation between the major philosophical schools and approaches to language teaching. There have been numerous methods to teaching language and the moment we talk of teaching a language, we know that we are talking about second or third language and not the first language. The following have been different methods used to teach second/third language: